PERAN ADVERTISING DAN CELEBRITIES PADA PURCHASE INTENTION DENGAN MELALUI BRAND AWARENESS - Salsabila Novia Azani; Yolanda Masnita (Indonesian Journal of Thousand Literacies, 2026)
Consumer purchase intention is a consumer who has the desire to buy or choose a product based on experience with the product. Advertisements and celebrities will influence purchase intention through brand awareness of sports shoes. The aims of this study were: (1) to analyze the effect of sports shoes advertising on purchase intention, (2) to analyze the effect of sports shoes advertising on purchase intention through brand awareness. (3) to influence the influence of celebrities on the intention to buy sports shoes. (4) to influence celebrity influence on purchase intention through brand awareness. and (5) to analyze the effect of brand awareness on purchase intention. This study used 153 samples obtained through non-probability sampling. Data was collected by distributing questionnaires. The test instrument used is in the form of validity and reliability tests. Data analysis used the goodness of fit test with the Amos program to answer the hypothesis. The results of the study show that advertisements and celebrities have a positive and significant effect on purchase intention through brand awareness.